Teaching practices in the pandemic: a view from bioecological development (Revista Contexto & Educação, 2022)
This paper focuses on the difficulties faced in remote education by four experienced teachers from the Elementary School and the facilitating mechanisms used by them during the coronavirus pandemic. In addition to being teachers, the participants simultaneously acted as mentors for beginning teachers in the Hybrid Mentoring Program (PHM). The data consists in responses collected in an online questionnaire, containing questions about the teaching performance in 2020. The analysis is based on the Bioecological Theory of Human Development (BRONFENBRENNER, 1994). The interrelationships, influences and impacts caused by micro-, meso-, exo-, macro- and chronosystems in the current context were considered in this study. Data analysis indicates that the participants faced difficulties, such as: lack of infrastructure; transpose knowledge about teaching adults how to teach into teaching children remotely; preparation of planning and evaluation; establishing relationships with students and their families; lack or delay in receiving directions from the school. The on-line networks, present both in the PHM microsystem and the school microsystem, were highlighted as an aid mechanism to the difficulties. In both contexts, the participants had the opportunity to exchange ideas and experiences for the construction of new learning about remote learning.
Keywords: Experienced teachers; Pandemic; Remote learning